Risk Management for 4-H Youth Development Work: Records and Contracts - Stefanie Prevatt; Dale Pracht; Paula Davis; Janet Psikogios; Marilyn Norman; Kate Fogarty; Jean Hink (EDIS, 2018)
This 2-page publication is one in the series Risk Management for 4-H Youth Development. This document will clarify the expectations and procedures for signature authority regarding contracts within UF/IFAS Extension. Written by Stefanie Prevatt, Dale Pracht, Paula Davis, Janet Psikogios, Marilyn Norman, Kate Fogarty, and Jean Hink and published by the UF/IFAS 4-H Youth Development Department, January 2018. http://edis.ifas.ufl.edu/4h295